Heme Polymerization Inhibitory Activity And Phytochemical Screening Of Ethyl Acetate Fraction In Manuran (Coptosapelta tomentosa Valeton ex K. Heyne) Stem - Arnida; Siti Humairah Z.A; Sutomo; Fadlillahturrahmah (Jurnal Jamu Indonesia, 2021)
The native Indonesian plant that is empirically used as an antimalarial agent is manuran (Coptosapelta tomentosa Valeton ex K. Heyne). This study aims to determine chemical compound and heme polymerization inhibitory activity of ethyl acetate fraction of C. Tomentosa stem based on IC50 value. The method identification of chemical compound used tube test, and the method of heme polymerization inhibitory activity was Basilico through in vitro method. The results of chemical compound identification of the ethyl acetate fraction of C. Tomentosa showed the presence of flavonoids, terpenoids, saponins, tannins, and anthraquinones. The average percentages of heme polymerization inhibitory activity of ethyl acetate fraction of C. Tomentosa stem from concentration 20; 10; 5; 2.5; 1.25; 0.625; 0.3125 mg / mL were 98.507; 97,872; 96,407; 93,560; 88,419; 80,680; and 45.467%.The averages of IC50 of ethyl acetate fraction and chloroquine diphosphate were 0.24 ± 0.018 mg/mL and 0.214 ± 0.012 mg/mL. This shows that the ethyl acetate fraction of C. Tomentosa stem has heme polymerization inhibitory activity. The result of the independent sample t-Test obtained the significance value of 0.111 (p more than 0.05) that there was no significant difference. It means that the ethyl acetate fraction of C. Tomentosa stem has heme polymerization inhibitory activity as well as chloroquine diphosphate. This suggests the potentiation of the methyl acetate fraction of the stem C. Tomentosa as anti-malarial.